The influence of media composition on the growth rate and cultural-morphological characteristics of Cladobotryum dendroides (Bull.) W. Gams & Hooz. strains - Medvedev, D. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
The influence of media composition on mycelium growth rate and cultural-morphological characteristics of 5 strains of fungicolous fungus Cladobotryum dendroides (Bull.) W. Gams & Hooz. (teleomorph of Hypomyces rosellus (Alb. & Schwein.) Tul. & C. Tul.). is considered. Pure cultures of different strains of Cladobotryum dendroides were isolated from carpophores of Agaricus bisporus (J.E. Lange) Imbach, which were collected in 5 different industrial mushroom farms of Ukraine. We studied the dependence of the growth rate of Cladobotryum dendroides mycelium and changes of its cultural and morphological characteristics on media composition – Chapek agar, potato-glucose agar, mushroom agar, in Petri dishes at temperature 18±1ºС. The radius of colonies was measured every day in two mutually perpendicular directions in order to estimate the radial growth rate (mm/day). The growth rate of the studied strains was maximal on the potato-glucose agar, strain 2 grew on the potato-glucose agar and Chapek agar with identical rate. Growth rate of strain 2 on the potato-glucose agar was higher than on the mushroom agar by 23%, and for strain 5 this difference was 80%. There was a difference of morphological features of strains colonies depending on composition of media: on the potato-glucose agar from the inoculum to the edge of the colony there were observed concentric ring-like formations, the edge of colony was distinctly outlined; on the Chapek agar radial strip-like formations of different expressiveness were from the inoculum and to the edge, the edge of colony was inexpressive; on the mushroom agar colonies had relatively large, pink inoculum of protuberant form, around it there was a white disk, from the middle and to the edge the colony was transparent, its edge was poorly outlined.